Blended learning as a strategy to improve sustainability and equity for professional development of rural teachers - Huang, Yanfen; Syed-Abdullah, Sharifah Intan Sharina; Zulkiflie, Nurul Nadwa; Ghazali, Norliza (Sciendo, 2024)
Teachers in rural areas should receive equal support and professional development training as those in urban areas. It is a strategy to promote education equity for the students in the former area. This study takes the learning experience and teaching practice experience of rural teachers who participated in the Rural Teacher Replacement Training Program (RTRTP) in Guangdong Province, China, as a case. Seventeen rural teachers who participated in the blended training program were chosen as a research sample. The effect of blended training was evaluated at four levels: participants’ reaction, participants’ learning, behavior, and learning results. A model of influencing factors for rural teachers’ blended training was developed. The results showed that rural teachers’ overall satisfaction with the blended training program was relatively high. Teachers reported a greater increase in knowledge skills, but the translation into practical knowledge and the impact on the organization was not as high as expected. Four dimensions and 14 main categories influence the blended training effect of rural teachers. This study provides a reference for improving the efficiency of rural teacher blended training, especially for promoting the teaching practice after teacher training.